Postoperative hemorrhagic occlusive retinal vasculitis associated with intracameral vancomycin prophylaxis during cataract surgery. Issue 11 (November 2016) - Miller, Matthew A.; Lenci, Lucas T.; Reddy, Chittaranjan V.; Russell, Stephen R.
Abstract : N/A: We present the case of a 75‐year‐old man who had uneventful cataract surgery and administration of intracameral vancomycin for endophthalmitis prophylaxis, followed by the same procedure in the fellow eye 1 week later. The patient subsequently developed bilateral hemorrhagic occlusive retinal vasculitis, resulting in profound vision loss in both eyes. A second case of hemorrhagic occlusive retinal vasculitis previously reported from our institution is summarized. That case was characterized by a far milder course, with rapid resolution of vision loss. The 2 cases illustrate the broad range of toxicity potentially associated with intracameral vancomycin, suggest that bilateral administration results in a worse prognosis, and indicate that this disorder may be underrecognized due to the potential for a mild course. We recommend that intracameral vancomycin not be used for endophthalmitis prophylaxis. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.